Third stage of labor placental complications and placenta-associated syndromes. (18th October 2021) - Rotem, Reut; Lipski, Alisa; Weintraub, Adi Y.; Baumfeld, Yael; Yohay, David; Press, Fernanda; Pariente, Gali
Abstract: Objective: To evaluate the association between third stage placental complications and placental insufficiency associated disorders, also known as, placenta associated syndromes. Study design: A population-based retrospective cohort study comparing placental-related perinatal outcomes of parturient with (study group) and without third stage placental complications, defined as a composite of retained placenta, adherent placenta, placenta accrete, need for manual removal of the placenta, postpartum curettage and revision of the uterine cavity. A univariate analysis was followed by a multivariable logistic regression model. Results: During the study period, 263, 023 deliveries met inclusion criteria, of which, 10, 281 (3.9%) experienced placental complications during the third stage of labor. Parturient in the study group had significantly higher rates of placental insufficiency associated disorders which included among others: hypertensive disorders of pregnancy (6.5 versus 5.6%, p < .001), stillbirth (1.9 versus 0.7%, p < .001) and preterm delivery (9.9 versus 7.7%, p < .001). Using a multivariable regression model, while controlling for confounders such as maternal age and induction of labor, third stage placental complications were independently associated with placental insufficiency associated disorders. Conclusion: Our findings suggest that placental associated adverse pregnancy outcomes and third stage placental complications may represent different manifestations of a common pathological or inadequate placentation process.